ASSESSMENT OF SAURIDA TUMBIL (BLOCH) STOCK IN THE NORTHWEST CONTINENTAL SHELF WATER OF INDIA - GULATI, D. K.; DEVARAJ, M.; GEORGE, J. P. (Journal of Indian Fisheries Association, 2015)
Based on the data collected from New Ferry Wharf, Sassoon Dock and exploratory survey of MFV Saraswati on the Northwest coast of India, the growth, mortality, population and stock parameters of Saurida tumbil is reported in the present communication. The Von Bertalanffy growth function (VBGF) parameters for growth on length were found to beL== 49.8 em, K = 0.96/year, to= -.141 year. The length at recruitment Or) is 80 mm. (tr = .167 year) while the length at first capture (lc) for the commercial trawl fishery is 100 mm (tc = 0.25 year). The annual fishing mortality coefficient (F) for 1983-85 was 0.43, the natural mortality coefficient (M) was 1.33 and the exploitation ratio (E) was 0.25. The yield per recruit (YIR) attained the maximum of 54.99 gat F = 1.091 forE = 0.45 for the present tc at 0.25 year. The annual total stock (P) and standing stock (P) in the exploitation portion at the inshore grounds to a depth of about 50 m were estimated to be 12,811 tons and 6,034 tons respectively. The average annual yield of 2,635 tons at the present F = 0.439 (E = 0.247) was less than the maximum sustainable yield (MSY) for 3,331 tons attainable from the inshore grounds at E = 0.45.